Toxicity of 17β-Estradiol to Green Algae and Cyanobacteria - JIANMENG, CHEN; JIANYI, MA; SENMIAO, TONG; PINWEI, WANG; WEI, CAO (Asian Journal of Chemistry, 2010)
The toxicity of various concentrations of 17b-estradiol to C. ellipsoidea and A. flos-aquae was studied. The results showed that there was a highly significant relationship between the dry weight or chlorophyll-a (chl-a) content and OD 680 nm for the algae tested. When the 17b- estradiol concentration was ³ 0.1 mg L-1 and £ 0.05 mg L-1 it inhibited and stimulated algal growth, respectively. EC50 decreased gradually from the 1st to the 7th days (18-104 mg L-1) for C. ellipsoidea and from the 1st to the 5th days (16-448 mg L-1) for A. Spiroides, then increased gradually from the 7th to the 15th days (31-104 mg L-1) for C. ellipsoidea and from the 5th to 10th days (16-155 mg L-1) for A. Spiroides. C. ellipsoidea was more sensitive than A. flos-aquae on the 1st to 3rd days and 7th to 10th days, but less sensitive on the 4th to 6th days. Both the toxicity and sensitivity were influenced by the testing time, implying that traditional algal tests (conducted at 72-96 h) do not provide sufficient information.